A multiplex lateral flow immunochromatography assay for the quantitative detection of pyraclostrobin, myclobutanil, and kresoxim-methyl residues in wheat. (30th May 2022) - Lin, Lu; Xu, Xinxin; Song, Shanshan; Xu, Liguang; Wu, Xiaoling; Liu, Liqiang; Kuang, Hua; Xu, Chuanlai
Highlights: Three mAbs with high specificity and sensitivity were prepared successful. A LFIA was fabricated for the detection of PYR, MYC, and KRE in wheat. The LOD was 2.5, 2.0, and 8.8 ng/g for PYR, MYC, and KRE, respectively. The developed LFIA can be used for quantitative detection of three drugs simultaneously. Abstract: We produced three monoclonal antibodies with high specificity and sensitivity, and developed a lateral flow immunochromatography assay (LFIA) for the qualitative and quantitative detection of pyraclostrobin (PYR), myclobutanil (MYC), and kresoxim-methyl (KRE) in wheat. In the qualitative analysis, the cut-off values of LFIA were 400, 200, and 800 ng/g for PYR, MYC, and KRE in wheat, respectively. Based on the results obtained from the membrane strip reader, we generated calibration curves for the quantitative analysis. PYR, MYC, and KRE monoclonal antibodies (mAbs) had half maximal inhibitory concentrations (IC50 ) of 25.4, 17.7, and 94.6 ng/g, respectively, and limit of detection (LOD) of 2.5, 2.0, and 8.8 ng/g, respectively. The linear detection scopes were 5.6–116.5, 4.2–74.4, 23.4–383.3 ng/g for PYR, MYC, and KRE, respectively. The intra-assay recoveries ranged from 89.2% to 101.7%, and the coefficients of variation ranged from 4.6% to 6.5%. The inter-assay recoveries ranged from 88.7% to 102.7%, with the coefficients of variation ranged from 7.2% to 9.1%. Thus, our developed LFIA is suitable for the qualitative and quantitative detection of PYR, MYC, and KRE residues in wheat.